Characterization of Arginine Kinase in the Barnacle Amphibalanus Amphitrite and Its Role in the Larval Settlement. Issue 4 (1st June 2016) - Zhang, Gen; Yan, Guo‐Yong; Yang, Xiao‐Xue; Wong, Yue‐Him; Sun, Jin; Zhang, Yu; He, Li‐Sheng; Xu, Ying; Qian, Pei‐Yuan
ABSTRACT: Energy metabolism is a key process in larval settlement of barnacles, but the underlying molecular mechanisms remain ambiguous. Arginine kinase (AK) mainly participates in energy metabolism in invertebrates. So far, its roles in barnacles have not been studied. In the present study, we raised an antibody against AK from Amphibalanus amphitrite Darwin to characterize the roles of AK in the larval settlement process. Among the developmental stages, AK was highly expressed during the cypris stage. Along with the aging process in cyprids, the level of AK decreased. The immunostaining results showed that AK was localized to muscular tissues in cyprids, including antennules, antennular muscles, and thoracic limbs. The larval settlement rate decreased and larval movement was inhibited in response to treatments with high concentrations of AK inhibitors (rutin and quercetin). These results demonstrated that AK was involved in the larval settlement of A. amphitrite through mediating energy supply in muscle tissues. Moreover, further analysis indicated that both the p38 MAPK and NO/cGMP pathways positively mediated the expression of AK in cyprids.